Docking of carbohydrates into protein binding sites - Agostino, Mark; Ramsland, Paul; Yuriev, E. (CRC Press, 2012)
Structures of protein–carbohydrate complexes can be investigated experimentally by x-ray crystallography or nuclear magnetic resonance (NMR) (Chapters 1 and 2). However, the crystallization of these complexes is often complicated by the inherent flexibility of carbohydrates, whereas NMR is more appropriate for the determination of conformation of bound carbohydrates rather than the nature of the interactions occurring with a protein. Computational molecular modeling techniques offer attractive alternatives for the study of protein–carbohydrate interactions. These techniques have been widely used in conformational studies of carbohydrates, as well as in the investigation of carbohydrate–protein recognition. Notably, molecular dock¬ing can provide insight into protein–ligand interactions in systems that are difficult to study experimentally.